OVEREXPRESSION OF SIALIDASE (NEU1) PROMOTES INTERLEUKIN-6 INDUCED INFLAMMATION IN HUMAN NEUROGLIA AND MONOCYTIC THP-1 CELLS - Chong, Taryne (My University, 2006)
Mammalian sialidases are hydrolytic enzymes that initiate the removal of terminal a2-3, a2-6 and a2-8 sialic acid residues from various sialylated glycoconjugates. Sialidases are reportedly involved in numerous cellular functions involving proliferation, differentiation, antigenic expression, inflammation and the tumorigenicity of malignant cells. Recently, sialidase has been implicated in various immune signaling pathways, involving immune effector cells, such as activated lymphocytes and macrophages. The human lysosomal sialidase gene encodes a 46 kD glycoprotein which exists in a multienzyme complex with β-galactosidase and PPCA. Neurodegenerative diseases such as Tay-Sachs and Sandhoff are characterized by the progressive storage of glycoproteins and sialylated oligosaccharides in the nervous system. The induction of inflammatory mediators is a critical step in the pathogenesis of neurodegeneration that remains largely undefined. As such, an in vitro model of Tay-Sachs disease was used to identify potential mediators involved in disease progression. In addition, we have used the THP-1 monocytic cell line as a model of human macrophages which play a key role in potentiating a variety of immune responses.
Translocation of neul from lysosomes to the cell surface and the resulting interaction with signaling molecules suggests neul is involved in the regulation of immune activities. We have investigated the role of sialidase on CD44 expression, an inflammation-associated glycoprotein found on the cell surface. Our data indicate that sialidase interacts with CD44 on the cell surface which may contribute to disease progression in Tay-Sachs disease. We illustrate that overexpression of sialidase stimulates interleukin-6 (IL-6) secretion in both human Tay-Sachs neuroglia and THP-1 derived macrophages. Moreover, the sialidase inhibitor 2-deoxy-2, 3-dehydro-N-acetylneuraminic acid (DANA) was found to attenuate IL-6 secretion and sialidase expression in THP-1 derived macrophages.
Keywords: SIALIDASE; INTERLEUKIN-6; INFLAMMATION; HUMAN NEUROGLIA; MONOCYTIC; THP-1 CELLS